Analisis Tingkat Pemahaman Mahasiswa Teknik Elektro Terhadap Materi Semikonduktor untuk Memenuhi Kebutuhan Industri: Studi Kasus di Universitas Lampung - Purwiyanti, Sri; Fitriawan, Helmy; Komarudin, M.; Alam, Syaiful (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The semiconductor industry is a strategic sector that plays a crucial role in supporting digital transformation and national technological independence. To build a competitive semiconductor ecosystem, it is essential to develop human resources (HR) with a strong understanding of semiconductor concepts and applications. This study aims to analyze the level of understanding among electrical engineering students regarding semiconductor materials as a foundation for strengthening HR capacity in this field. A qualitative approach was applied through a survey involving 35 students of the Electrical Engineering Department, University of Lampung, specializing in Electronics and Control. The survey instrument consisted of a questionnaire with three answer categories: “do not know,” “know but cannot explain,” and “know and can explain,” covering four main themes—semiconductor physics, semiconductor technology, IC design, and semiconductor applications. The results revealed that most students only mastered basic concepts, while understanding of more advanced materials remained limited. These findings indicate the need to improve learning effectiveness through more interactive and contextual methods, along with the enrichment of materials relevant to industry needs. The results of this study are expected to provide valuable insights for strengthening semiconductor education in higher institutions to support the growth of Indonesia’s semiconductor industry.